PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU ABORSI KEHAMILAN AKIBAT PERKOSAAN BERGILIR (GANG RAPE) - Hidayat, Tommy; Rai Setiabudhi, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 01, Maret 2014)
Gang rape is a crime that could pregnancy to the victim. Therefore, abortion is the top choice of the victims to avoid public gossip. But, abortion also regulated in the Penal Code, it means the Penal Code prohibits the act of abortion. Purpose of this study was to determine how the perpetrators of abortion as well as a victims of crime Therefore it is necessary normative juridical assessment of the legislation relating to the crime of abortion. With the regulation of abortion in the Penal Code, largely determine how to given legal protection and accountability abortionists who are victims of criminal acts of gang rape.
Keywords: Abortion. Legal Protection, Gang Rape